Crystallization of poly(l‐lactic acid) in solution with the mosquito‐repellent N, N‐diethyl‐3‐methylbenzamide. Issue 1 (3rd October 2018) - Sungkapreecha, Chanita; Iqbal, Naeem; Focke, Walter W.; Androsch, René
Abstract: Poly(l ‐lactic acid) (PLLA) can be used as a carrier for the mosquito repellent N, N ‐diethyl‐3‐methylbenzamide (DEET). PLLA dissolves in DEET at elevated temperature and crystallizes on cooling to below the concentration‐dependent equilibrium melting temperature, leading to scaffold formation. In this work, non‐isothermal and isothermal crystallization experiments were performed, using differential scanning calorimetry and polarized‐light optical microscopy. Crystallization of PLLA in solution with DEET is faster than melt‐crystallization of neat PLLA, with the maximum crystallization rate decreasing with decreasing PLLA content in the investigated range from 5 to 50 m% PLLA. The decrease of the maximum crystallization rate with increasing solvent content is due to decreases in both the maximum crystal growth rate and the nuclei density. The observed downward shift of the temperature range of crystallization is caused by the depression of equilibrium melting temperature and a strong decrease of the glass transition temperature, both occurring with increasing solvent concentration. It is assumed that the strong decrease of the glass transition temperature due to the presence of DEET, and the related increase of the mobility of PLLA chains, is the main reason for the increased crystallization rate compared to melt‐crystallization of PLLA. It is demonstrated that a large variety of spherulitic superstructures can be obtained by variation of the crystallization conditions, presumably leading to largely different 3D scaffold structures and DEET‐delivery characteristics. Abstract : Crystallizable PLLA dissolves in the mosquito‐repellent DEET at elevated temperature and undergoes a solid‐liquid thermally‐induced phase separation on cooling. Variation of the conditions of solution‐crystallization of PLLA allows largely different semicrystalline morphologies to be obtained at ambient temperature, from space‐filled spherulitic to isolated spherulites embedded in a DEET‐rich continuous phase, with impact expected on the evaporation behavior of the drug.